Measuring innovation: the use of indicators in developed countries. Issue 3 (13th July 2015) - Al-Mubaraki, Hanadi Mubarak; Muhammad, Ali Husain; Busler, Michael
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to describe and identify the ranking of innovation program landscape in the UK. The identification will focus on the average of four categories: policy, culture, economy, and industry. Design/methodology/approach – The nature of this research is mainly qualitative. This investigation uses two semi-structured interview based in the UK, combined with an examination of organizational documents. Findings – The research findings indicated highest ranking of the Petchey Center of Entrepreneurship located in University of East London present culture 60 percent, policy 75 percent, industry 80 percent, and economy 100 percent. Originality/value – The authors conclude with several recommendations for academia and practitioners such as governments, policy makers, funded organizations, and strategic institutions.